The Application of Log-Periodicity Theory in Forecasting Financial Crashes - Górski, Maciej (Journal of Finance and Financial Law, 2014)
The main purpose of this article is to apply the newest forecast methods of financial crashes based on fractal analysis. The article includes short review of log-periodicity formulas and the research which shows the forecasting efficiency of these formulas referring to extremely different (in the size, development etc.) financial markets. Considerations refer to following problem: share price trajectories contain certain log-periodicity patterns which indicate the lack of share market efficiency. This problem is also induced by specific investor’s behavior. This behavior in combination with speculators activities are the main reasons of creating bubbles and financial crashes.